Pengaruh Kebijakan Dividen dan Konservatisme Akuntansi terhadap Kualitas Laba - Dewi Retno Mumtaz; Suwarno Suwarno (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This research aims to examine the effect of dividend policy and accounting conservatism on earnings quality in companies in the infrastructure, utilities & transportation and mining sectors listed on the Indonesia Stock Exchange (BEI). This type of research is quantitative research. The sampling method used is a purposive sampling method based on certain criteria. From the specified criteria, a sample of 25 companies was obtained. The analytical method used is multiple linear regression analysis using IBM SPSS statistics 22. The results of this research indicate that the dividend policy variable has no effect on earnings quality. Meanwhile, accounting conservatism has a significant positive effect on earnings quality. The principle of accounting conservatism is applied by companies on the basis of management's caution against exaggerating the profit value of the financial statements.